A violência conjugal em contextos de ruralidades: um estudo com mulheres rurais de comunidades do interior de Minas Gerais - Aline Gomes Martins (2017)
The present work is about a doctoral research carried out with rural women from communities in the interior of Minas Gerais. To carry out the research it was necessary to go through three stages, exposed in the articles that compose this thesis. The first one, presented in the first article, includes a bibliometric review aimed at ascertaining the relationship between domestic violence and alcohol from the periodicals available on the CAPES portal published between 2003 and 2013. The review found that marital violence stands out among the forms of expression of violence, with the woman being the potential victim. In addition, the number of articles that contemplate the conjugal violence in rurality contexts is scarce. In this sense, based on the results of the bibliometric review, a research proposal was developed whose general objective was to understand the meanings of conjugal violence and related practices according to women living in rural communities of two cities in the interior of Minas Gerais, presented in the second article of this thesis. To access the subjects of the study, contact was made with the Basic Health Units (BHUs) that cover the rural areas of the two cities. The Community Health Agents (CHA's) provided information on cases of marital violence in the rural communities in question. After six months of immersion in the field interviews were conducted with twelve women. The interviews were submitted to content analysis. The Theory of Social Representations guided the study and mainly the discussion of the results. It was observed that: the women interviewed represented violence as the extreme of the injury produced to the other, relating the idea of violence to death and physical aggression; Psychological and physical violence stood out among the types of violence suffered; The alcohol and jealousy of the aggressor were pointed out by women as factors associated with violence; The mother was mentioned as the main support of women; All children witnessed and suffered violence experienced by women in their different forms of manifestation. In addition, it was observed that the women developed different strategies of survival in face of the experiences of violence that they experience daily. In addition, in view of the experience in the communities in question and contact with the women interviewed, it was necessary to discuss the process of doing research, especially the immersion in the field and the interviews, which is the third article of this thesis.